Current understanding and the potential future of spinal fusion - Sharma, Krishna (Nepal Journal of Neuroscience, 2023)
Pathologies of spine like trauma, infection, malignancy or congenital problems can cause disturbed structural integrity of spine causing deformity and displacement of spine. This causes compression or damage on spinal cord and roots, which the spine is supposed to protect. In such situations, the spine needs to be decompressed, realigned and fused in that position, so that further injury is prevented. Spinal fusion is a natural process of healing of bones where the structural stability is restored. However, the alignment and strength achieved by natural process of fusion may be inadequate and slow, with persistent compression on neural structure. Natural process of spinal fusion, thus may need to be correctly re-aligned and then further fixed by grafts and instruments. To achieve faster and stronger fusion, the process may need to be further augmented by pharmacological agents, graft expanders and graft enhancers.